A systematic review of eating disorder prevalence in the Nordic countries: 1994–2016. Issue 3 (3rd July 2018) - Dahlgren, Camilla Lindvall; Stedal, Kristin; Wisting, Line
Abstract: Objective: The objective of this study was to systematically review the literature on eating disorder prevalence in the Nordic countries (i.e. Denmark, Finland, Iceland, Norway and Sweden) between 1994 and 2016.Method: Three online databases, PubMed, PsycINFO and SveMed+, searches were conducted, targeting articles on prevalence, incidence and epidemiology of eating disorders (EDs). The review was performed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and was limited to International Classification of Diseases 10th revision (ICD-10) and the Diagnostic and Statistical Manual of Mental Disorders 4th Edition (DSM-IV) ED diagnoses published between 1994 and 2016.Results: A total of 19 studies fulfilled inclusion criteria and were included in the study. Results revealed that anorexia nervosa (AN) and binge eating disorder (BED) prevalence ranges in females are lower in the Nordic countries compared to Europe in general, and slightly higher for bulimia nervosa (BN).Discussion: The current review shows that there is an imperative need for studies investigating the prevalence of EDs in the Nordic countries by employing a methodology which allows for a formal diagnosis. The notable lack of two-stage designs in the studies reviewed renders concern regarding the validity of the obtained prevalence rates. It is essential that future studies employ standardized methodologies as these will allow for comparison across geographic regions, genders and ages, facilitating mapping of prevalence rates over time.